A 8-mer Peptide of PGLYRP1/Tag7 Innate Immunity Protein Binds to TNFR1 Receptor and Inhibits TNFα-Induced Cytotoxic Effect and Inflammation - Telegin, Georgii B.; Chernov, Aleksandr S.; Kazakov, Vitaly A.; Romanova, Elena A.; Sharapova, Tatiana N.; Yashin, Denis V.; Gabibov, Alexander G.; Sashchenko, Lidia P. (Frontiers in Immunology, 2021)
Search for novel regulatory protein fragments with potential functional roles is required both for understanding the immune response mechanisms and the development of targeted immunotherapy. Earlier we demonstrated that the PGLYRP1/Tag7 innate immunity protein can be regarded as an inhibitor of TNFα cytotoxic activity via the interaction with its TNF receptor 1 (TNFR1). A C-terminal peptide fragment 17.1 of the molecule is responsible for this function. In this study we have identified a minimal 8-mer region of this peptide (hereinafter – 17.1A) capable to bind to TNFR1. As a result of such interaction, the cytotoxic signals induced by this receptor are blocked. Also, this peptide demonstrates an anti-inflammatory activity in vivo in the complete Freund’s adjuvant (CFA)-induced arthritis model in laboratory mice. Peptide 17.1A is capable to reduce periarticular inflammation, inhibit the development of synovitis and exhibit a protective effect on cartilage and bone tissues. This peptide can turn out to be a promising medicinal agent for autoimmune arthritis and other diseases.